Defending Land Rights: A Study of Agrarian Conflict in Pengudang Village, Bintan Regency, Kepulauan Riau Province - Rani Medisa; Heni Hardianti; Yogi Pranata; Nikodemus Niko (UIN Siber Syekh Nurjati Cirebon, 2025)
The land conflict between the residents of Pengudang Village and PT Buana Megawisatama (BMW) in Bintan Regency dates back to 1993, whenthe company offered compensation to local residents to relinquish their land at disproportionately low prices, accompanied by promises ofresidential plots and housing, most of which were never fulfilled. This imbalance triggered mounting tensions and protests from the community, culminating in demonstrations involving university students and resulting in repressive actions by security forces. This study aims to examine the root causes of the conflict in depth and to evaluate the effectiveness of various resolution efforts undertaken, including mediation and directinterventions by relevant stakeholders. Data were collected through in-depth interviews with informants selected via snowball sampling. The findings reveal that this conflict reflects structural tensions between local communities and corporate interests over access to and control of land, with significant social, economic, and environmental repercussions for the affected population. Despite the local government’s mediation efforts and land retribution initiatives.